Principles of supply chain management - Crandall, Richard E., 1930-; Crandall, William, 1956-; Chen, Charlie C., Ph. D. author (Boca Raton : CRC Press/Taylor & Francis Group, 2010)
"An increasingly global business landscape means that even the smallest of companies must contend with a growing base of international suppliers and customers. With that comes myriad technical, organizational, and cultural changes that challenge traditional management practices. Regardless of the means taken to address these challenges, all companies will eventually have to synchronize the flow of their products, information, and funds." "Going beyond the usual supply chain text, Principles of Supply Chain Management not only details the individual components of the supply chain but also illustrates how the pieces must come together for an effective supply chain." "Focusing on the customer and working backwards through distribution, manufacturing, and the extractive industries of mining and agriculture, the text provides numerous examples and case histories to outline a proven approach for achieving effective supply chain integration. This self-contained resource provides readers with a realistic appraisal of the state of the art in supply chain management and the understanding needed to build and manage effective supply chains in a wide-range of industries. Most importantly, it emphasizes the need for building and maintaining cooperation and collaboration among all members of the supply chain."--BOOK JACKET.
Evolution of supply chains -- Supply chains as a system -- Determining customer needs -- Distribution and retailing -- Production and service processes -- Procurement/purchasing -- Reverse supply chains -- The need to integrate -- Why integration is difficult -- How to build an integrated supply chain -- Information flow along the supply chain -- Funds flow along the supply chain -- ROI for supply chains and other issues -- Trends in supply chain development and management -- Preparation for the future.
Includes bibliographical references and index.
Keywords: Business logistics; Physical distribution of goods -- Management; Marketing channels -- Management